1987
DOI: 10.1063/1.451984
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the reaction O(1D2)+H2→OH(X 2Π,v″=2,3)+H: Full characterization of product energetics

Abstract: Articles you may be interested inFull characterization of OH product energetics in the reaction of O(1 D 2) with hydrocarbons J. Chem. Phys. 95, 8166 (1991); 10.1063/1.461296 The effect of reagent excitation on the dynamics of the reaction O(1 D 2)+H2→OH(X 2Π)+H J. Chem. Phys. 95, 8038 (1991); 10.1063/1.461284 Reaction dynamics of O(1 D 2)+H2, HD, D2: OH, OD(X 2Π i ) product internal energy distributions J. Chem. Phys. 84, 5365 (1986); 10.1063/1.449947 H+D2 reaction dynamics. Determination of the product state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…The general trend in the excitation data is similar to that reported by others [e.g., Mikulecky and Cericke, 1992;Smith and Butler, 1980;Butler et al, 1986;Cleveland et al, 1987] for this range of rotational levels. The excitation rate is found to increase approximately linearly with increasing rotational level and then fall off at total internal energies near the reaction exoergicity.…”
Section: Discussionsupporting
confidence: 76%
“…The general trend in the excitation data is similar to that reported by others [e.g., Mikulecky and Cericke, 1992;Smith and Butler, 1980;Butler et al, 1986;Cleveland et al, 1987] for this range of rotational levels. The excitation rate is found to increase approximately linearly with increasing rotational level and then fall off at total internal energies near the reaction exoergicity.…”
Section: Discussionsupporting
confidence: 76%
“…IS ExperimentaP-3,6,16,17 and molecular dynamics simulation studies 8 ,18-24 have demonstrated that the simplest ofthese 0* reactions, that with H2 in Eq. (2), proceeds via insertion of 0* into the H-Hbond to yield HOH, 6,16,17,25 with subsequent decomposition of the chemically activated intermediate leading to production of highly excited OH molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Preferential population of Å(A 0 ) states has also been observed for dissociation of water initiated by the chemical reaction ( Butler et al 1986;Cleveland et al 1987;Alexander et al 2004 (Harich et al 2000). Calculations by Dixon (1995) and Dixon et al (1999) addressing these dissociation channels imply that for slow molecular rotation of H 2 O, the Å (A 0 ) states dominate, with the effect being strongest in the limiting case of the nonrotating parent.…”
Section: Discussionmentioning
confidence: 91%